Application of activated sludge for odor control in wastewater treatment plants: Approaches, advances and outlooks. (15th August 2020) - Fan, Fuqiang; Xu, Ronghua; Wang, Depeng; Meng, Fangang
Abstract: Odors from wastewater treatment plants (WWTPs) have attracted extensive attention and stringent environmental standards are more widely adopted to reduce odor emissions. Biological odor treatment methods have broader applications than the physical and chemical counterparts as they are environment-friendly, cost-effective and generate low secondary wastes. The aqueous activated sludge (AS) processes are among the most promising approaches for the prevention or end-of-pipe removal of odor emissions and have the potential to simultaneously treat odor and wastewater. However, AS deodorization biotechnologies in WWTPs still need to be further systematically summarized and categorized while in-depth discussions on the characteristics and underlying mechanisms of AS deodorization process are still lacking. Recently, considerable studies have been reported to elucidate the microbial metabolisms in odor control and wastewater treatment. This paper reviews the fundamentals, characteristics, advances and field experiences of three AS biotechnologies for odor treatment in WWTPs, i.e., AS recycling, microaeration in AS digester and AS diffusion. The underlying deodorization mechanisms of typical odors have been revealed through the summary of recent advances on multi-element conversions, metabolic interactions of bacteria, microscopic characterization and identification of functional microorganisms. Future research aspects to advance the emerging deodorization AS process, such as deodorization mechanisms, simultaneous odor and water treatment, synergistic treatment with other air emissions, are discussed. Graphical abstract: Image 1 Highlights: Activated sludge (AS) processes are promising in odor control. Polysulfide plays an important role in H2 S production. Poly-S is stored intracellularly or extracellularly in biological sulfur conversions. Chemical and biochemical deodorization mechanisms were revealed. Diverse future aspects of the emerging deodorization AS process were proposed.